Socio-spatial transformations and territorial appropriation of Ipeúna, state of São Paulo, Brazil region - de Carvalho, Mara Lígia Scotton [UNESP] (Universidad de Jaen, 2023)
It analyzes the socio-spatial transformations and the territorial appropriation of the region that encompasses the municipality of Ipeúna and areas near the borders with its bordering municipalities. It establishes the period between the 17th and 20th centuries as a temporal cutout. It searches for answers to identify the main agents that acted in the occupation process and in the fragmentation of the territory of this region. It identifies, understands and analyzes the transformations that occurred after the constitution of the first roads, the donated lands, and follows the buying and selling processes that took place through the first official records of their dismemberment; in parallel, it contextualizes the agents that caused the organization of this space. The study uses as tools primary documentation, the theoretical basis, oral reports, iconography, and cartographic material. It contributes to diminish the existing gaps in the historiography of the beginning of the territorial occupation of the Ipeúna region, with the purpose of registering and substantiating a history that has not yet been written.
Transformaciones socioespaciales y la apropriación territorial de la región Ipeúna, estado de São Paulo, Brasil
Transformations socio-spatiales et appropriation territoriale de la région Ipeúna, état de São Paulo, Brésil
Keywords: Ipeúna/SP/Brazil; Paths; Space Organization; Territorial Appropriation; Transformations